2021
DOI: 10.1002/jqs.3401
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene–Holocene climatic implications of high‐resolution stable isotope profiles of a speleothem from south‐central Anatolia, Turkey

Abstract: High-resolution 230 Th ages and stable isotope (δ 18 O and δ 13 C) records from a stalagmite that grew between 39 and 2 ka in Incesu Cave located in south-central Anatolia allow us to evaluate paleoclimate conditions for growth periods during Marine Isotope Stage 3 (MIS3) and the Holocene. High δ 18 O values and Heinrich events H3 and H4 are observed during the MIS3 interval. After a dry period in the Younger Dryas, low values between ca. 10 and 5.3 ka suggest a transition to wet mid-to early Holocene conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 87 publications
(218 reference statements)
1
6
0
Order By: Relevance
“…This isotopic source effect is expressed in the Soreq, Peqiin (Bar-Mathews et al, 2003; Bar-Mathews and Ayalon, 2011; Burstyn et al, 2022), and Jeita Cave records (Verheyden et al, 2008; Cheng et al, 2015), with more negative oxygen isotope values following the depletion of sea-surface δ 18 O as resolved from planktonic foraminifera (Grant et al, 2016). In the southern Taurus Mountains, both Dim (Unal-Imer et al, 2015) and Incesu Cave records (Erkan et al, 2022) show a trend toward more depleted δ 18 O from ~10 to ~8 ka. Although the isotopic composition of the EM source is considered to have a primary effect on the δ 18 O signal of the terrestrial records, the isotopic δ 18 O depletion is amplified by increased rainfall (Emeis et al, 2003; Almogi-Labin et al, 2009), also leading to more negative δ 18 O values.…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…This isotopic source effect is expressed in the Soreq, Peqiin (Bar-Mathews et al, 2003; Bar-Mathews and Ayalon, 2011; Burstyn et al, 2022), and Jeita Cave records (Verheyden et al, 2008; Cheng et al, 2015), with more negative oxygen isotope values following the depletion of sea-surface δ 18 O as resolved from planktonic foraminifera (Grant et al, 2016). In the southern Taurus Mountains, both Dim (Unal-Imer et al, 2015) and Incesu Cave records (Erkan et al, 2022) show a trend toward more depleted δ 18 O from ~10 to ~8 ka. Although the isotopic composition of the EM source is considered to have a primary effect on the δ 18 O signal of the terrestrial records, the isotopic δ 18 O depletion is amplified by increased rainfall (Emeis et al, 2003; Almogi-Labin et al, 2009), also leading to more negative δ 18 O values.…”
Section: State Of the Artmentioning
confidence: 99%
“…This isotopic source effect is expressed in the Soreq, Peqiin (Bar-Mathews et al, 2003;Bar-Mathews and Ayalon, 2011;Burstyn et al, 2022), and Jeita Cave records (Verheyden et al, 2008;Cheng et al, 2015), with more negative oxygen isotope values following the depletion of sea-surface δ 18 O as resolved from planktonic foraminifera (Grant et al, 2016). In the southern Taurus Mountains, both Dim (Unal-Imer et al, 2015) and Incesu Cave records (Erkan et al, 2022) show a trend toward more depleted δ 18 O from ∼10 to ∼8 ka. Although the isotopic composition of the EM source is considered to have a primary effect on the δ 18 O signal of the terrestrial records, the isotopic δ 18 O depletion is amplified by (Torfstein et al, 2013a(Torfstein et al, , 2013b, Soreq Cave (Bar- Matthews et al, 2003;Burstyn et al, 2022), Zalmon Cave (Keinan et al, 2019), Peqiin Cave (Bar- Matthews et al, 2003), Mizpe Shelagim (MS) Cave (Ayalon et al, 2013), Ammiq peat record (Hajjar et al, 2010), Jeita Cave (Verheyden et al, 2008;Cheng et al, 2015), Yammouneh basin (Develle et al, 2010), El-Jurd peat record (Chedaddi and Khater, 2016), Ghab core (Van Zeist and Woldring, 1980;Yasuda et al, 2000), Sağlik peat (Sekeryapan et al, 2020), Incesu Cave (Erkan et al, 2022), Dim Cave (Ünal-Imer et al, 2015, LC21 (Grant et al, 2012), and ODP 967 (Emeis et al, 2003;Scrivner et al, 2004).…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Speleothem-based paleoclimate studies in Türkiye are mostly focused on the last ice age or the Holocene period, some with important linkages with early human settlements (Fleitmann et al, 2009; Göktürk et al, 2011; Rowe et al, 2012; Ünal-İmer et al, 2015, 2016a; Koç et al, 2020; Erkan et al, 2021; Jacobson et al, 2021, 2022). The oldest records from the region are from Sofular (Badertscher et al, 2011) in NW Türkiye and Dim Cave (Rowe et al, 2020) from SSW Türkiye.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Yelini Cave, the evaporation component in the P−E balance might be important due to atmospheric circulation at the geographical location of the studied cave. The barrier effect of the mountain ranges in the northern and southern parts of Türkiye prevents moisture from moving inland(Erkan et al, 2021), resulting in a prevalence of semi-arid climatic conditions around Yelini Cave.In arid and semi-arid areas, near-surface evaporation processes are reflected as seasonal variations in δ18 O (McDermott et al, 2006, and references therein). Schemmel et al (2013) reported a modern meteoric water study suggesting that the general trend of increase in δD and δ 18 O from the sheltered sides of the mountain ranges in the southern and northern parts of Türkiye to the interior Central Anatolian Plateau (CAP) is the result of increased sub-cloud and surface evaporation due to drought conditions.…”
mentioning
confidence: 99%